Solution of Zadeh's Fast Way Problem Under Z-Information - Aliyev, Rashad R.; Adilova, Nigar E. (Springer International Publishing Ag, 2020)
The concept of Z-numbers introduced by Prof. L. Zadeh created the new approach to decision-making problem. Use of Z-information for describing and calculating uncertain information was more convenient and decision making under Z-information was more adequate. Zadeh's achievements on base of Z-information became a source of motivation for other researchers. In this paper we propose the solution method for Zadeh's fast way problem under Z-information. This solution method is based on Z-dynamic programming approach. To illustrate this problem under Z-information, the numerical example is analyzed.
10th International Conference on Theory and Application of Soft Computing, Computing with Words and Perceptions (ICSCCW) -- AUG 27-28, 2019 -- Prague, CZECH REPUBLIC
Keywords: Z-numbers; Z-information; Z-dynamic programming; Fast way problem